COVID PANDEMIC AND INDIAN ECONOMY; A STUDY ON TOURISM AND PHARMACEUTICAL INDUSTRY - Mohd Aasif Bhat; Waseem Gani; Aejaz Ahmad Mir (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
Abstract This study aims to assess the impact of the covid-19 pandemic on the Indian economy by analysing its effects on tourism and the pharmaceutical industry. The effects of covid pandemic across the sectors and in various situations of partial and complete lockdown. The paper relies on the secondary source of data related to various sectors during pandemics and explains the profit and loss of these sectors in the pandemic. The economy of India may barely figure out to have 0.5% positive growth in an optimistic like situation for the FY 2020, but also faces a negative growth rate of 3 to 7%. The manufacturing sector shrinks to 20% from 5.5%. The effects of covid-19 are severe tourism, but the pharmaceutical industry has exponentially and positively grown up.